CANONICAL GROUPOIDS WITH \(x^m · y^n = xy\) - Čupona, Ǵorǵi; Celakoski, Naum; Janeva, Biljana (Matematichki Bilten, 1999)
We give a convinient description of free objects in the variety of groupoids with the axiom \(x^m · y^n = xy\).